Model of Student Leadership Skills Development in the 21st Century, Roi - Et Municipality Schools - Seeme, Bussaba; Dongchatom, Kritkanok; Ruangsuwan, Chayakan (Interdisciplinary Academic and Research Journal, 2023)
Changes in the 21st century, the leadership and Sufficiency Economy Philosophy are important in the development of students' leadership that is consistent with the global society in the 21st century and the Sufficiency Economy Philosophy, which the researcher has foreseen the problems and applied to research. This research aimed to 1) study background and the desired 21st-century student leadership skills, 2) develop a 21st-century student leadership skills model, and 3) study the findings of the implementation of the developed 21st-century student leadership skills model in Roi-Et Municipality schools. The sample group for this research was 104 teachers from 4 lower secondary schools—Wat Sa Thong Municipality School, Watpa Rerai Municipality School, Nong Ya Ma Municipality School, and Waruwan Municipality School. The tools used in this research were questionnaires. Mean and standard deviation (S.D.) were the statistics used in analyzing the collected data. The research findings were 1) the result of the implementation of the developed 21st-century student leadership skills model, in terms of 4 decision-making skill-related elements, were at high levels; 2) the result of the implementation of the developed 21st cent21st-century leadership skills model, in terms of 4 team building skill related elements, were at high levels; 3) the result of the implementation of the developed 21st-century student leadership skills model, in terms of 3 responsibility skill related elements, were at high levels; and 4) the result of the implementation of the developed 21st-century student leadership skills model, in terms of 5 relationship skill related elements, were at high levels.